Development of Arduino UNO Based Automated Storage and Retrieval System - Parab, Anuradha S.; Gore, P. N. (Asian Review of Mechanical Engineering, 2020)
Automated storage and retrieval system (AS/RS) is prototyped to take account of effect of various dwell point strategies and locations of input-output station on expected travel time and throughput of system. The effect of shape function on expected cycle time and throughput of system. Arduino UNO microcontroller is used to control and operate storage and retrieval functions. Arduino UNO software provides complete package of flexible programming platform for control operation of input output devices. Android interfacing to control system provides smarter rand easily accessible human control panel.